Effect of rapid ventricular pacing on cerebral oxygenation in transcatheter aortic valve implantation (Tavi): Role of routine near-infrared spectroscopy monitoring - Karaaslan, Pelin; Darçın, Kamil; Özyüksel, Arda; Kutlu, Esra; Köse, Emine Arzu; Boztosun, Bilal; Akçevin, Atıf (Scientific Publishers of India, 2017)
Objective: Transcatheter aortic valve implantation has become an important treatment modality in patients with high risk comorbidities for surgical aortic valve replacement. The objective of this study is to evaluate the cerebral perfusion status using near infrared spectroscopy method especially during the rapid ventricular pacing phase of the transcatheter aortic valve implantation procedure. Methods: 20 consecutive patients undergoing trans-femoral aortic valve implantation procedure between May 2015 and March 2016 in our institute were retrospectively evaluated. The periprocedural cerebral oxygenation was measured with a near infrared spectroscopy sensor (INVOSTM-5100 C, Medtronic Inc., Minneapolis, MI, USA) located on the forehead of the patients. All hemodynamic data and cerebral near infrared spectroscopy values were recorded before, during and after the procedure with constant time intervals, especially at the time of rapid ventricular pacing and device deployment. Results: The mean age was 74.4 ± 9.2 years. Male female ratio was 1.8 to 1 (13 males, 7 females). Mean procedure time was 70.2 ± 14.3 minutes. The rapid ventricular pacing included two episodes with a total time for pacing of 22.6 ± 5.1 seconds. There was a statistically significant difference with regard to the heart rate and the cerebral near infrared spectroscopy values (p=0.006 and p=0.02; respectively) in all patients during the rapid ventricular pacing period. The cerebral near infrared spectroscopy values were statistically lower than baseline levels (p<0.001). Conclusion: This observational study presents the significant decrease of cerebral near infrared spectroscopy values during the rapid ventricular pacing phase of the transcatheter aortic valve implantation procedure. Further studies may reveal cut-off values both for near infrared spectroscopy values and rapid ventricular pacing duration in order to determine a critical cut-off level.
Keywords: Aortic Valve Stenosis; Cardiac Pacing; Cerebral Ischemia; Cerebrovascular Stroke; Near Infrared Spectroscopy; Transcatheter Aortic Valve Implantation